PERAN SATUAN BINTAL KODAM DALAM PEMBINAAN MENTAL ROHANI ISLAM BAGI PRAJURIT DI KODAM XVII CENDERAWASIH PAPUA - Muhammad Irwan Putra (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This study used a qualitative approach with descriptive analysis. The data that the researchers obtained were based on the results of observations and interviews with informants. The results of the study showed that the role of the Bintaldam unit in carrying out Islamic mental and spiritual development for soldiers was shown by carrying out various series of routinely programmed activities so that soldiers in the Cenderawasih Regional Military Command XVII unit had a good spiritual mentality. The supporting factors for the proper implementation of this program and maximum results include the support from the Bintaldam unit leaders who synergize with each other in implementing the Bintaldam program that has been designed as well as with the facilities and infrastructure available to support various mental development activities for soldiers.